2023
DOI: 10.1039/d3tb00439b
|View full text |Cite
|
Sign up to set email alerts
|

Multicellular spheroids containing synthetic mineral particles: an advanced 3D tumor model system to investigate breast precancer malignancy potential according to the mineral type

Abstract: Mineral particles that form in soft tissues in association with disease conditions are heterogeneous in their composition and physiochemical properties. Hence, it is challenging to study the effect of mineral...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 64 publications
0
4
1
Order By: Relevance
“…Another variant examined was S-HA, which consists of spherical nanocrystalline HA particles. Unlike previous findings, S-HA did not stimulate cell proliferation, whether presented as individual particles or as aggregates . These differences can likely be attributed to differences in cell-to-mineral ratios, underscoring the need for meticulous consideration of experimental conditions when investigating cell-mineral interactions.…”
Section: Resultscontrasting
confidence: 87%
See 2 more Smart Citations
“…Another variant examined was S-HA, which consists of spherical nanocrystalline HA particles. Unlike previous findings, S-HA did not stimulate cell proliferation, whether presented as individual particles or as aggregates . These differences can likely be attributed to differences in cell-to-mineral ratios, underscoring the need for meticulous consideration of experimental conditions when investigating cell-mineral interactions.…”
Section: Resultscontrasting
confidence: 87%
“…Previous in vitro studies have shown that exposure to HA in 2D cell culture systems can lead to increased cellular mitogenesis, proliferation rates, enhanced cell adhesion, upregulated matrix metalloproteinase activity, and elevated secretion of pro-osteoclastic interleukin-8 (IL-8). , Additionally, exposure to HA crystals has resulted in the enlargement of multicellular spheroids resembling tumor-like structures and increased Her2 expression in precancerous breast cells . In this study, we examined six distinct minerals as CaP analogues to assess their impact on the proliferation of DCIS cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reliable in vitro cancer models are often considered powerful tools for studying the mechanisms of cancer development, assessing the efficacy of new drugs and understanding potential approaches to cancer treatment. 1,2 The demand for three-dimensional (3D) in vitro models is steadily increasing, driven by the necessity to capture the intricate complexity of tumor biology and drug development more effectively compared to traditional two-dimensional (2D) cultures. 2,3 3D culture systems provide a more realistic biochemical and biomechanical microenvironment, offering not only a comprehensive overview of tumor cell signaling in vivo but also enabling faithful reproduction of human tumor cell-matrix interactions in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The demand for three-dimensional (3D) in vitro models is steadily increasing, driven by the necessity to capture the intricate complexity of tumor biology and drug development more effectively compared to traditional two-dimensional (2D) cultures. 2,3 3D culture systems provide a more realistic biochemical and biomechanical microenvironment, offering not only a comprehensive overview of tumor cell signaling in vivo but also enabling faithful reproduction of human tumor cell-matrix interactions in vitro . 4 Individual tumor cells integrate numerous external cues, including those from various extracellular matrix (ECM) structures, components, mechanical stimuli, and soluble signals from neighboring or distant cells, to generate their fundamental phenotype and adapt to changes in the microenvironment.…”
Section: Introductionmentioning
confidence: 99%